2023
DOI: 10.1136/bjsports-2022-106176
|View full text |Cite
|
Sign up to set email alerts
|

European fitness landscape for children and adolescents: updated reference values, fitness maps and country rankings based on nearly 8 million test results from 34 countries gathered by the FitBack network

Abstract: Objectives(1) To develop reference values for health-related fitness in European children and adolescents aged 6–18 years that are the foundation for the web-based, open-access and multilanguage fitness platform (FitBack); (2) to provide comparisons across European countries.MethodsThis study builds on a previous large fitness reference study in European youth by (1) widening the age demographic, (2) identifying the most recent and representative country-level data and (3) including national data from existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 63 publications
(130 reference statements)
0
26
0
Order By: Relevance
“…Our findings showed that children and adolescents in a certain age group performed better, compared to international norms [ 17 ]. This has been confirmed in the most recent European study, which positions Croatia as having “intermediate” level of cardiorespiratory fitness (16 th place out of 34 countries studied) with percentile ranks of 58.1 and 52.5 for boys and girls, respectively [ 28 ]. However, a study by Tomkinson et al .…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…Our findings showed that children and adolescents in a certain age group performed better, compared to international norms [ 17 ]. This has been confirmed in the most recent European study, which positions Croatia as having “intermediate” level of cardiorespiratory fitness (16 th place out of 34 countries studied) with percentile ranks of 58.1 and 52.5 for boys and girls, respectively [ 28 ]. However, a study by Tomkinson et al .…”
Section: Discussionmentioning
confidence: 55%
“…Although biological aspects explaining the differences between boys and girls in the cardiorespiratory fitness have been well-described [ 17 ], it is necessary to put into perspective our newly reference data for Croatia and compare them with international norms [ 17 , 28 ]. In a systematic review by Tomkinson et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations